Cladonia lichens and their major metabolites as possible natural antioxidant, antimicrobial and anticancer agents - Kosanic, Marijana; Ranković B.; Stanojkovic, Tatjana; Rančič A.; Manojlovic, Nedeljko (LWT - Food Science and Technology, 2014)
The aim of this study is to investigate invitro antioxidant, antimicrobial, and anticancer activities of the acetone extracts of the lichens Cladonia furcata, Cladonia pyxidata and Cladonia rangiferina and their atranorin and fumarprotocetraric acid constituents. Antioxidant activity was evaluated by free radical scavenging, superoxide anion radical scavenging, reducing power, and determination of total phenolic and flavonoid compounds. As a result of the study atranorin had largest free radical scavenging activity with IC50 values 131.48μg/mL. Moreover, the tested samples had effective reducing power and superoxide anion radical scavenging. Total content of phenol and flavonoid in extracts was determined as pyrocatechol equivalent, and as rutin equivalent, respectively. The strong relationships between total phenolic and flavonoid contents and the antioxidant effect of tested extracts were observed. The antimicrobial activity was estimated by determination of the minimal inhibitory concentration by the broth microdilution method. The most active was fumarprotocetraric acid with minimum inhibitory concentration values ranging from 0.031 to 0.125mg/mL. Anticancer activity was tested against FemX (human melanoma) and LS174 (human colon carcinoma) cell lines using MTT method. All samples were found to be strong anticancer activity toward both cell lines with IC50 values ranging from 10.97 to 41.23μg/mL. © 2014 Elsevier Ltd.